Phytochemical Investigations on the Hydro-alcoholic Stem Fractions of Viburnum Linn. Species - Prabhu, K.; Karar, P.K.; Hemalatha, S.; Ponnudurai, K.; Singh, Pooja (Asian Journal of Chemistry, 2011)
The genus Viburnum Linn. under the family-Caprifoliaceae (formerly) and Adoxaceae (recently) have been reported to contain about 17 species in India and been reported to possess remarkable biological activities against smooth muscle related troubles and microbial infections (protozoal and bacterial in origin). Three species were collected from Nilgiri hills, Tamilnadu, India and the aqueous ethanolic extracts of the stems of these species were tested for their antibacterial spectrum, which exhibited a significant activity against S. aureus, V. cholerae and E. coli, at a concentration of 800 μg/mL. In particular, V. erubescens (one of the species) was far more potent against P. aeruginosa at all concentrations (25-800 μg/mL), when compared to the other species as well as the reference (gentamycin, 25-800 μg/mL). To explore the chemical nature of the constituents responsible for antibacterial activity, an experiment was employed to isolate the phyto-constituents from the aqueous ethanolic stem extracts. A preliminary organic analysis on the alcoholic stem extracts showed the presence of phenolic compounds such as flavonoids, tannins, anthocyanins, phenolic acids and their derivatives (glycosides) as their principal constituents, which may be attributed to a mild and the pronounced antibacterial ativities of the extracts. In order to unfold the chemistry of constituents of the extracts, the residues were fractionated in a column chromatography with solvents of increasing polarity followed by a gradient elution of components by methanol-water mixtures of decreasing polarity. About three phenolic compounds were isolated in pure form and spectroscopically characterized (UV, IR, NMR and Mass) to be ferulic acid, arbutin and chlorogenic acid from V. punctatum, V. coriaceum and V. erubescens, respectively.